Предмет:
МатематикаАвтор:
анонима) (25 х а – а х b2) = a x (25 – b2) = a x (52 – b2) = a x (5 – b) x (5 + b).
Ответ: 25 х а – а х b2 = a x (5 – b) x (5 + b).
б) (3 x a2 – 6 x a – 3) = 3 x (a2 – 2 x a – 1) = 3 x (a – 1)2 = 3 x (a -1) x (a – 1).
Ответ: (3 x a2 – 6 x a – 3) = 3 x (a -1) x (a – 1).
в) a2 + 5 x a + 5 x b – b2 = (a2 – b2) + (5 x a + 5 x b) = (a – b) x (a + b) + 5 x (a + b) = (a + b) x (a – b +5).
Ответ: a2 + 5 x a + 5 x b – b2 = (a + b) x (a – b +5).
Автор:
izabelleДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть